BRCC3 promotes activation of the NLRP6 inflammasome following cerebral ischemia/reperfusion (I/R) injury in rats. (21st June 2021) - Huang, Xiaohuan; Gan, Hui; Tan, Junyi; Wang, Tingting; Zhao, Jing; Zhao, Yong
Highlights: BRCC3 is involved in cerebral ischemia/reperfusion injury. BRCC3 affects the inflammatory response following cerebral ischemia/reperfusion injury. BRCC3 influences activation of the NLRP6 inflammasome. Further studies are needed to confirm the molecular mechanism by which BRCC3 regulates NLRP6. Abstract: NOD-like receptor family pyrin domain containing 6 (NLRP6), a novel member of the NLR family, has been confirmed to have an inflammasome-dependent proinflammatory effect in cerebral ischemia/reperfusion injury. NLRP6 assembles a multimeric inflammasome complex comprising the adaptor ASC and the effector pro-caspase-1 to mediate the activation of caspase-1. The molecular mechanism regulating activation of the NLRP6 inflammasome remains unclear. Previous studies have shown that BRCA1-BRCA2-containing complex subunit 3 (BRCC3), a JAMM domain-containing Zn 2+ metalloprotease deubiquitinating enzyme, participates in a variety of cellular activities. In this study, we found that BRCC3 expression was increased in the middle cerebral artery occlusion (MCAO) model. BRCC3 siRNA could reduce nerve damage and inflammation. Interestingly, the result of co-immunoprecipitation showed that the interaction between BRCC3 and NLRP6 was enhanced after model, and the result of immunofluorescence showed that the co-localization of BRCC3 and NLRP6 was increased. At the same time, the expression of NLRP6, cleavated-caspase-1 and IL-1β was decreased after BRCC3 interference. These results illustrate a regulatory mechanism involving the BRCC3-NLRP6 pathway and highlight NLRP6 as a potential therapeutic target for inflammatory diseases.